Mid-term results of surgical interventions of high-grade vena cava tumor thrombus - ÖZTÜRK, FATİH; AK, KORAY; TİNAY, İLKER; ARSAN, SİNAN (My University, 2022)
© 2022 All right reserved by the Turkish Society of Cardiovascular Surgery. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes (http://creativecommons.org/licenses/by-nc/4.0/).Background: This study aims to investigate whether the coexistence of advanced renal cell carcinoma and inferior vena cava tumor thrombus could be treated with a multidisciplinary approach and teamwork and to evaluate early and mid-term results. Methods: Between January 2017 and December 2020, a total of 33 patients (28 males, 5 females; mean age: 55.8±13.2 years; range, 27 to 76 years) who underwent radical nephrectomy and thrombectomy of the inferior vena cava were retrospectively analyzed. Demographic characteristics of the patients, types of operations, postoperative data, mortality and morbidity rates were recorded. Results: Of the patients, 12% (n=4) had Stage 2 tumor thrombus, 60.6% (n=20) had Stage 3 tumor thrombus, and 27% (n=9) had Stage 4 tumor thrombus. A total of 55% (n=19) of the patients had right-sided renal cell carcinoma, while 45% (n=14) of them had a left-sided mass. Totally, 66% (n=22) of the patients underwent primary inferior vena cava repair. The thrombectomy procedure and a Dacron® patch was applied with patch plasty in 24% (n=8) of the patients, and Dacron® graft interposition was applied to the inferior vena cava in 9% (n=3) of the patients. The mean follow-up was 20.3±13.0 (range, 2 to 70) months. Deep vein thrombosis was detected in the follow-up of seven (21%) patients, and no pulmonary thromboembolism was observed during the postoperative follow-up period. The mean length of stay in the intensive care unit was 1.39±0.6 (range, 1 to 3) days. The 30-day mortality rate was 3%, due to the loss of one patient from massive pulmonary embolism intraoperatively. Conclusion: Vascular surgical procedures performed regardless of the stage of the tumor thrombus provide satisfactory mid-term results in patients with advanced renal cell cancer.

Amaç: Bu çalışmada, renal hücreli karsinom ve inferior vena kava tümör trombüs birlikteliğinin multidisipliner bir yaklaşım ve ekip çalışması ile tedavi edilip edilemeyeceği araştırıldı ve erken ve orta dönem sonuçları değerlendirildi. Çalışma planı: Ocak 2017 - Aralık 2020 tarihleri arasında, radikal nefrektomi ile birlikte inferior vena kavaya trombektomi uygulanan toplam 33 hasta (28 erkek, 5 kadın; ort. yaş: 55.8±13.2 yıl; dağılım, 27-76 yıl) retrospektif olarak incelendi. Hastaların demografik özellikleri, ameliyat türleri, ameliyat sonrası verileri, mortalite ve morbidite oranları kaydedildi. Bulgular: Hastaların %12’sinde (n=4) Evre 2 tümör trombüsü, %60.6’sında (n=20) Evre 3 tümör trombüsü, %27’sinde (n=9) Evre 4 tümör trombüsü vardı. Hastaların toplam %55’inde (n=19) sağ taraflı renal hücreli karsinom ve %45’inde (n=14) sol taraflı kitle mevcuttu. Hastaların toplam %66’sında (n=22) inferior vena kava primer olarak onarıldı. Hastaların %24’üne (n=8) trombektomi ve yama plasti ile Dacron® yama uygulandı ve %9’una (n=3) inferior vena kavaya Dacron® greft interpozisyonu yapıldı. Ortalama takip süresi 20.3±13.0 (dağılım, 2-70) ay idi. Yedi (%21) hastanın takibinde derin ven trombozu saptandı ve ameliyat sonrası takip döneminde pulmoner tromboemboli saptanmadı. Yoğun bakım ünitesinde ortalama kalış süresi 1.39±0.6 (dağılım, 1-3) gün idi. Bir hasta ameliyat sırası masif pulmoner tromboemboli nedeniyle kaybedildiği için 30 günlük mortalite oranı %3 idi. Sonuç: İleri evre renal hücreli kanser hastalarında tümör trombüsünün evresinden bağımsız olarak yapılan vasküler cerrahi işlemler tatmin edici orta vadeli sonuçlar sağlar.
Yüksek dereceli vena kava tümör trombüsünde cerrahi müdahalelerin orta dönem sonuçları
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Cardiovascular; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; SOLUNUM SİSTEMİ; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; RESPIRATORY SYSTEM; CARDIAC & CARDIOVASCULAR SYSTEMS; Cerrahi; Akciğer ve Solunum Tıbbı; Kardiyoloji ve Kardiyovasküler Tıp; Surgery; Pulmonary and Respiratory Medicine; Cardiology and Cardiovascular Medicine; Cardiopulmonary bypass; renalcellcarcinoma; thromboendarterectomy; vena cava; RENAL-CELL CARCINOMA; CANCER; EXTENSION; RESECTION; OUTCOMES; VEIN; Renal cell carcinoma; Thromboendarterectomy; Vena cava; :Cardiopulmonary bypass; renal cell carcinoma; thromboendarterectomy; vena cava; Kardiyopulmoner baypas renal hücreli karsinom; tromboendarterektomi; vena kava